Anxiety, past trauma and changes in relationships in Japan during COVID-19. (July 2022) - Goodwin, Robin; Takahashi, Masahito
Abstract: Widely shared traumas have the potential to both improve and impair our relationships with others. During COVID-19 anxiety has been seen as a major individual vulnerability associated with relationship change, as have the wider economic, situational factors facing families and communities. In this national sample of 997 Japanese respondents we assessed perceived relationship changes in couple relations, neighbourhood relations, and wider relations with Japanese nationals, alongside anxiety, exposure to previous mass traumas, household economics, education, and vulnerability to COVID-19. Whilst most respondents reported little change in their relationships during this year there was a small overall improvement in couple relationships and a decline in relations with wider communities. Participant's economic resources were positively associated with an improvement in couple relationships, while anxiety was associated with a decline in relations with both the neighbourhood and the wider society. While neither prior experience of mass trauma, nor education or health vulnerability to COVID-19, were associated with relationship change, having time to talk, and younger age, was positively associated with improvement in couple relations. Findings suggest that anxiety can function to distance relationships during a time of stress, but perceived changes in relationships are little effected by experience of previous trauma. Relationship growth is likely to be greatest in those with better economic conditions. Practitioners need to be mindful of the impact of enhanced anxiety during the pandemic on interpersonal relations, and a potential threat to the relationships of older couples during this time of pandemic threat.